53. Electrophysiological characterization in adult form Niemann-Pick type C disease. Issue 1 (January 2015) - Iodice, R.; Dubbioso, R.; Topa, A.; Santoro, L.; Manganelli, F.
<x xml:space="preserve">Abstract</x> In infantile and juvenile NPC disease electrophysiological studies have shown central (CNS) and peripheral (PNS) nervous system abnormalities. However, an extensive electrophysiological evaluation of CNS and PNS in adult form of NPC is still lacking. To assess in Niemann-Pick type C disease (NPC) the involvement of the central (CNS) and peripheral (PNS) nervous system by a multimodal electrophysiological approach. Three patients affected by adult form of NPC underwent electrophysiological evaluation including nerve conduction study (NCS), motor (MEPs) and somatosensory (SEPs) evoked potentials at upper and lower limbs, visual (VEPs) and brainstem auditory (BAEPs) evoked potentials. NCS, VEPs, MEPs and upper limb SEPs were normal. Lower limb SEPs were abnormal in all patients and abnormalities were consistent with a central somatosensory pathway involvement (CCT: 21.2 ± 0.6 ms). BAEPs were constantly abnormal with peripheral and central type lesions. Our electrophysiological findings are in keeping with pathological evidence of dysfunction at brainstem level between acoustic nerve and inferior colliculus/superior olivary nucleus for auditory pathways and at gracile nuclei for somatosensory pathways. Moreover, our results, unlike cases of infantile and juvenile NPC disease, suggest the sparing of PNS and of visual and corticospinal pathways.